Spray Freeze‐Drying as an Alternative to the Ionic Gelation Method to Produce Chitosan and Alginate Nano‐Particles Targeted to the Colon. Issue 12 (25th August 2015) - Gamboa, Alexander; Araujo, Valeria; Caro, Nelson; Gotteland, Martin; Abugoch, Lilian; Tapia, Cristian
Abstract : Chitosan and alginate nano‐composite (NP) carriers intended for colonic delivery containing prednisolone and inulin were obtained by two processes. Spray freeze‐drying using chitosan (SFDC) or alginate (SFDA) was proposed as an alternative to the traditional chitosan–tripolyphosphate platform (CTPP). NPs were fully characterised and assessed for their yield of particles; level of prednisolone and inulin release in phosphate and Krebs buffers; and sensitivity to degradation by lysozyme, bacteria and faecal slurry. NPs based on chitosan showed similar properties (size, structure, viscoelastic behaviour), but those based on SFDC showed a higher mean release of both active ingredients, with similar efficiency of encapsulation and loading capacity for prednisolone but lower for inulin. SFDC was less degraded in the presence of lysozyme and E. coli and was degraded by B. thetaiotaomicron but not by faecal slurry. The results obtained with SFDA were promising because this NP showed good encapsulation parameters for both active ingredients and biological degradability by E. coli and faecal slurry. However, it will be necessary to use alginate derivatives to reduce its solubility and improve its mechanical behaviour. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:4373–4385, 2015